Blood Flow Restriction Therapy after Closed Treatment of Distal Radius Fractures - Cancio, Jill M.; Sgromolo, Nicole M.; Rhee, Peter C. (Journal of Wrist Surgery, 2019)
Background Blood flow restriction (BFR) therapy is an innovative rehabilitative program that enables patients to increase strength at a fraction of the weight typically necessary in endurance exercises. Therefore, we conducted a pilot study evaluating patient outcomes with a BFR therapy program for closed management after a distal radius fracture compared to a traditional rehabilitation protocol.Literature review A randomized-controlled study was conducted comparing a standardized hand therapy rehabilitation protocol alone to a combined protocol with the use of BFR therapy in patients who were initially treated with closed reduction and short arm cast immobilization for a displaced distal radius fracture between May 1, 2015 and August 1, 2016. BFR therapy was performed with a restrictive tourniquet applied to the upper brachium, performing the same strengthening exercises as the control group but with the restrictive tourniquet in place. Clinical assessment was conducted at 6, 10, and 14 weeks from the date of initial cast immobilization. Outcome measures collected included wrist range of motion; grip strength; pinch strength; visual analogue scale for pain with activity and at rest; patient-rated wrist evaluation (PRWE) scores; and disabilities of the arm, shoulder, and hand scores.Results Thirteen patients were enrolled and randomized between the BFR (n = 6) and control (n = 7) groups. The BFR group noted significantly greater reduction in pain with activity compared to the control group after 8 weeks of therapy (Δ −4.0 vs. −2.3, p = 0.03). Similarly, patients in the BFR group displayed greater reduction in PRWE scores compared to the control group after 8 weeks of BFR therapy (Δ −57.9 vs. 30.8, p = 0.01). The two groups did not demonstrate any significant difference in radiographic outcomes at any time point or throughout the course of the study. All patients tolerated the BFR therapy program and there were no complications.Clinical relevance The addition of BFR therapy to the rehabilitative program after closed management of a distal radius fracture is safe, well tolerated by patients, without any deleterious effects on radiographic outcomes. This pilot study noted that BFR therapy in patients with nonoperative distal radius fractures may result in a larger reduction in pain with activity and greater improvement in overall self-perceived function.
Keywords: distal radius fracture; blood flow restriction therapy; fracture rehabilitation